The character education of the novel “Rantau 1 Muara” - Yasin, Achmad (ARKA INSTITUTE, 2023)
This research method uses a qualitative descriptive method with analytical techniques. The research object used is the novel Rantau 1 Muara by Ahmad Fuadi. This research focuses on researching the values of character education which include religious values, honesty, hard work, creativity, curiosity, love of the motherland, respect for friendship, friendship/communicative, fond of reading, and social care. Data collection techniques were carried out by means of researchers reading, understanding, determining each element of the novel intrinsic and extrinsic. Then the researcher determines every statement from the characters contained in the novel and then analyzes it and applies it in learning literature in high school. The results of this study can be concluded that there are 77 value statements of character education which are divided into 7 religious values, 5 honest values, 8 hard work values, 6 creative values, 4 curiosity values, 8 love the country values, 5 respect achievement values, 21 values friendly/communicative, 6 values fond of reading, and 7 values social care. In this study, friendly/communicative values dominate, this has been proven by the many algorithms that refer to these values.